A STUDY TEACHER’S TALK IN A CLASSROOM INTERACTION IN “SMAN 01 PONTIANAK - Banu, Supartina Margarita; Sada, Clarry; Sudarsono, Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research was designed to analyze the teacher’s talk in a classroom interaction. It refers to how the teacher managed their time or opportunity in terms of talking in front of the classroom. It was to answer: a) how long the teacher used the English language; b) what expressions the teacher explained the material; c) and how the classroom interaction was. The researcher adapted FIAC (Flanders interaction analysis categories system) to analyze the data. The data were collected through observation, questionnaire, and interview. The findings showed that the talk was still dominated by the teacher. It was only few opportunities for the students to talk. The interaction was not based on: teacher-student interaction and student-student interaction, but teacher based interactionKeywords: teacher’s talk, classroom, interaction